Damping micromechanisms for bones above room temperature - Lambri, Osvaldo Agustin F. (2014)
The wide damping maximum which is reported to appear in bones, involving bothcortical and cancellous parts, between around 280 K and 420 K; has been determined to be acomposition of different processes taking place at different temperatures in cancellous and corticalparts. In fact, in the present work the mechanical response of cow ribs bones has been analysed by coupling mechanical spectroscopy, differential scanning calorimetry, thermogravimetry andscanning electron microscopy studies. Cancellous part develops two damping maxima at around 320 K and 350 K. Cortical part exhibits a wide maximum in damping between around 310 K and 410 K and another damping relaxation between 390 K and 410 K. The physical-chemical driving force giving rise to the above relaxation processes are discussed.